Pengembangan Sistem Informasi Peminjaman Alat Laboratorium Berbasis Android dan Realtime Database Menerapkan Framework FAST - Dimas Jayadi; Ucuk Darusalam (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Practical tools are one of the lecture facilities that are at risk of being damaged or lost, so a system for recording borrowing and returning transactions is needed so that the existence of borrower data and tools can be known. Therefore, an android-based information system was designed as a medium for borrowing and returning laboratory equipment, to make it easier to borrow tools, record equipment borrowing, and inventory laboratory equipment. The method used in this research is the FAST (Framework for the Application Systems Thinking) method. This application is built using the Java programming language and utilizes the Firebase Real-time Database for data storage and processing. The application of this android-based information system has had a positive impact on laboratory assistants and colleagues in the process of borrowing and returning equipment. In addition, for the Computer Vision laboratory assistant Multimedia, this information system helps in carrying out inventory and maintenance of lab equipment.